Occurrence of fungi in bean seeds ‘Red Mexican’ and its effect on the germination - Ferreira, Deziany da Silva; Pires, Luana Martins; de Oliveira, Thiago Alves Santos; Peixoto, Nei; Carvalho, Daniel Diego Costa (Scientia Agraria Paranaensis, 2017)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->The seed-born fungi can be transmitted to long distances, for the transport of the same, in addition to harming seed viability. Therefore, the objective of this study was to verify the occurring fungi on common bean ‘Red mexican’ seed and evaluate its effect in the development of normal seedlings. Therefore, stored bean seeds ‘Red mexican’ were submitted to blotter test in four different dates. The design was completely randomized (CRD) and each assessed data had eight replicates. Each experimental unit (repetition) consisted in a Gerbox containing 25 seeds. The fungi incidence and development of normal seedlings were evaluated at 5 and 7 days, respectively. It was verified a larger incidence for Aspergillus sp. (19% to 57%) when compared to Cladosporium cladosporioides (11% to 29%). The incidence of the fungi Aspergillus sp. and C. cladosporioides did not interfere in the percentage of normal seedlings, due to the escape mechanism of the seedlings to pathogens during the germination process.